Pengaruh Iklim Organisasi Dan Motivasi Kerja Terhadap Kepuasan Kerja Pegawai Pada Kantor Kementerian Agama Kabupaten Lebak - Indah Lestari; Mila Triani (Universitas La Tansa Mashiro, 2020)
This study aims to determine the effect of Organizational Climate and Motivation either partially or simultaneously on Employee Job Satisfaction at the Office of the Ministry of Religion, Lebak Regency.The independent variable in this study is organizational climate and work motivation and the dependent variable is job satisfaction.The method used in this research is quantitative method which is analyzed using multiple linear analysis. The sample was taken by simple random sampling method with the Yamane formula where the respondents were 56 people. The data collection technique uses a questionnaire that has been tested for validity and reliability. The statistical test used is data normality testing, multicollinearity, heterocdasticity, autocorrelation, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, hypothesis testing (t test) using the help of the SPSS V 21 program.The results showed that partially organizational climate has no positive effect but has a significant effect on job satisfaction. And the research results show that motivation has a positive and significant effect on job satisfaction. Meanwhile, simultaneously or together that organizational climate and work motivation affect job satisfaction at the Office of the Ministry of Religion, Lebak Regency. The dominant variable that affects job satisfaction is work motivation.The conclusion from the results of the recapitulation of responses is categorized as quite good, namely, the responses of respondents regarding Organizational Climate with a percentage of 80.2%, Work Motivation having a percentage of 73.6%. And Job Satisfaction has a percentage of 73% which is good enough. Organizational climate and work motivation together have a positive and significant effect on job satisfaction.